Effect of placental cord drainage on third stage of labour and in prevention of postpartum hemorrhage: randomized control trial at tertiary care centre - S. N., Srujana Lakshmi; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Postpartum hemorrhage is the leading cause associated with 25% of maternal mortality. Prolonged duration of third stage of labour accounts for postpartum hemorrhage. The new trend in third stage management is placenta cord drainage (PCD). The physiology of PCD is decrease in bulkiness of placenta which consequently increases the uterine contractility. Effective uterine contraction mostly shortens third stage duration and decrease the risk for PPH Methods: This study is a randomized control trial in which full term pregnant women admitted in labour unit at Sri Devaraj Urs medical college and research centre, Kolar, Karnataka. Total 80 women were included in this study. They were divided into two groups, control group and study group with n=40 in each group. Placental cord drainage was done in the study group. In the Group 1 placental end of the cut umbilical cord remained clamped. In the Group 2, the placental end of the cut umbilical cord unclamped immediately and collected in a vessel till the flow ceased. Thus, the drained blood was prevented from getting mixed with blood lost in the third stage. Blood lost in the third stage was collected in a clean drape sheet. Placenta was delivered by controlled cord traction after the signs of placental separation were seen. The duration of third stage was calculated using a stopwatch. Results: In our study, the mean duration of third stage of labour in control group was 6.58minute and in study group was 2.28 minutes. Significant statistical difference was found in duration of third stage of labour. Conclusions: PCD is noninvasive and safe intervention during third stage of labour and effective in reduction of incidence of postpartum hemorrhage.